2020
DOI: 10.1177/1369148120910984
|View full text |Cite
|
Sign up to set email alerts
|

Profiling foreign policy leaders in their own language: New insights into the stability and formation of leadership traits

Abstract: Leaders matter in international politics. One of the main tools for assessing at-a-distance psychological characteristics of political leaders is Leadership Trait Analysis. To facilitate empirical studies, a Leadership Trait Analysis coding scheme for automated text analysis was developed to replace hand-coding. However, the coding scheme has been available only for English-language texts. To broaden research opportunities, this article presents a novel Leadership Trait Analysis coding scheme for the German la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 25 publications
0
11
1
Order By: Relevance
“…Considering that the speeches themselves span the period in which Putin first came to power as President, are mostly directed towards a domestic audience, and prioritize domestic policy, this research will contend that that in-group bias and task-orientation were likely to be higher in this sample than would be represented in a larger and more varied dataset. This is due to the fact that previous LTA research has indicated that task-orientation is affected when a leader assumes a new position and that in-group bias score is correlated with its usefulness in policy (Cuhadar et al, 2017b;Personality, Hermann, 2002;and Rabini, 2020). The speeches analyzed, from least amount of content to most, were Putin's December 1999 New Year's address, Putin's inauguration speech of January 2000, Putin's June 2000 press-conference with former US President Clinton and Russian media following the US-Russian summit, and Putin's annual address to the Federal Assembly of the Russian Federation in July 2000.…”
Section: Effects Of Context On Subsequent Trendsmentioning
confidence: 99%
“…Considering that the speeches themselves span the period in which Putin first came to power as President, are mostly directed towards a domestic audience, and prioritize domestic policy, this research will contend that that in-group bias and task-orientation were likely to be higher in this sample than would be represented in a larger and more varied dataset. This is due to the fact that previous LTA research has indicated that task-orientation is affected when a leader assumes a new position and that in-group bias score is correlated with its usefulness in policy (Cuhadar et al, 2017b;Personality, Hermann, 2002;and Rabini, 2020). The speeches analyzed, from least amount of content to most, were Putin's December 1999 New Year's address, Putin's inauguration speech of January 2000, Putin's June 2000 press-conference with former US President Clinton and Russian media following the US-Russian summit, and Putin's annual address to the Federal Assembly of the Russian Federation in July 2000.…”
Section: Effects Of Context On Subsequent Trendsmentioning
confidence: 99%
“…Greene and Cross (2017), for example, trace the evolution in the agenda of the European Parliament by developing a dynamic topic model of speeches from Members of European Parliament during 1999-2014. In another application, Rabini et al (2020) develop a coding scheme for leadership trait analysis in the German language to examine the influence of leadership on German foreign policy using computational text analysis. Text analysis has also been used to study issue framing-such as in the case of biofuel policy in Brazil (Talamini & Dewes, 2012)-as well as its influence on public attitude, for example, in the case of austere fiscal policy in Britain (Barnes & Hicks, 2018).…”
Section: F I G U R Ementioning
confidence: 99%
“…Most importantly, the addition of new languages to automated content analysis of LTA now presents another potential growth area for this approach. Rabini et al (2020) successfully illustrate this development in their coding with German documents. The Brummer et al (2020) forum include the authors' reports about experimenting with automated coding (of LTA and operational code) in multiple other languages (specifically, Arabic, German, Persian, Spanish, and Turkish).…”
mentioning
confidence: 96%
“…This research grew significantly in its geographic span as well: scholars profiled leaders from many non-English speaking countries (Dyson and Raleigh, 2014;He and Feng, 2013;Malici, 2008;Malici and Buckner, 2008;Kesgin, 2013;2019;2020a;2020b;Özdamar and Canbolat, 2018). Presently, the addition of new languages in automated content analysis (Brummer et al, 2020;Canbolat, 2021;Rabini et al, 2020) promises new advancements in leadership studies and foreign policy analysis. Arguably not receiving as much attention, there has also been work that offers new paths and connections with other topics of inquiry.…”
mentioning
confidence: 99%